(untitled) (Scientific journal of the Fergana State University, 2025)
This article is devoted to the study of the mechanisms of the creative thinking process within the framework of neurolinguistics. The biophysiological and mental mechanisms of complex thinking, serendipity and insight as forms of creative thinking in the subcortical sphere and neocortex of the brain substance are characterized.